Crofelemer, an Antisecretory Antidiarrheal Proanthocyanidin Oligomer Extracted from Croton lechleri, Targets Two Distinct Intestinal Chloride Channels - Tradtrantip, Lukmanee; Namkung, Wan; Verkman, A.S. (Molecular pharmacology, 2010)
Crofelemer, a purified proanthocyanidin oligomer extracted from the bark latex of Croton lechleri, is in clinical trials for secretory diarrheas of various etiologies. We investigated the antisecretory mechanism of crofelemer by determining its effect on the major apical membrane transport and signaling processes involved in intestinal fluid transport. Using cell lines and measurement procedures to isolate the effects on individual membrane transport proteins, crofelemer at 50 μM had little or no effect on the activity of epithelial Na+ or K+ channels or on cAMP or calcium signaling. Crofelemer inhibited the cystic fibrosis transmembrane regulator (CFTR) Cl− channel with maximum inhibition of ∼60% and an IC50 ∼7 μM. Crofelemer action at an extracellular site on CFTR produced voltage-independent block with stabilization of the channel closed state. Crofelemer did not affect the potency of glycine hydrazide or thiazolidinone CFTR inhibitors. Crofelemer action resisted washout, with <50% reversal of CFTR inhibition after 4 h. Crofelemer was also found to strongly inhibit the intestinal calcium-activated Cl− channel TMEM16A by a voltage-independent inhibition mechanism with maximum inhibition >90% and IC50 ∼6.5 μM. The dual inhibitory action of crofelemer on two structurally unrelated prosecretory intestinal Cl− channels may account for its intestinal antisecretory activity.